2023
DOI: 10.3390/admsci13070162
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Change: The Challenge of Change Aversion

Abstract: Organizational change has been investigated for decades, with many works addressing change adoption challenges. Change aversion, like change resistance, is not uncommon, but going unchecked can reduce organizational change initiative success. This communication aims to provide a concise in-road for students and practitioners to the organizational change and change aversion literature. An attempt is made to enter this complicated discussion in a way that may assist the reader in understanding what change aversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
0
13
0
1
Order By: Relevance
“…Many stakeholders, including manufacturers, employees, healthcare professionals, and consumers, may not fully understand the environmental and social impacts of pharmaceutical production or the potential benefits of sustainable practices. Building awareness, providing training programs, and promoting knowledge-sharing are essential to overcome this challenge [55,67,78]. Shifting towards sustainable practices requires a cultural shift within pharmaceutical companies.…”
Section: Current Challenges In Drug Manufacturing Sustainabilitymentioning
confidence: 99%
“…Many stakeholders, including manufacturers, employees, healthcare professionals, and consumers, may not fully understand the environmental and social impacts of pharmaceutical production or the potential benefits of sustainable practices. Building awareness, providing training programs, and promoting knowledge-sharing are essential to overcome this challenge [55,67,78]. Shifting towards sustainable practices requires a cultural shift within pharmaceutical companies.…”
Section: Current Challenges In Drug Manufacturing Sustainabilitymentioning
confidence: 99%
“…Systems of oppression, for example, are often characterized by very high levels of resilience and effectively resist change. While transformative change is not always the most appropriate response to a crisis, investigations of organizational change have shown that resistance, aversion, inertia and commitment to the status quo are significant impediments (Hubbart, 2023). Moreover, communication process are generally recognized as important factors in successfully change management (Daly et al, 2003).…”
Section: Further Questions Propositions and Applicationsmentioning
confidence: 99%
“…Resistencia al Cambio Organizacional: La resistencia al cambio por parte de empleados y gestores puede obstaculizar la adopción de tecnologías digitales. Este fenómeno a menudo está arraigado en el temor a lo desconocido y en la percepción de que la nueva tecnología podría alterar las dinámicas laborales existentes o amenazar los puestos de trabajo (Hubbart, 2023). 4.…”
Section: Mejora En La Producción Industrialunclassified